Case Study of an Attention Deficit/Hyperactivity Disorder Patient - Meity Meganita; Satiningsih Satiningsih (International Conference on Psychology and Education (ICPE), 2024)
Attention Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder in which individuals experience persistent problems of inattention and/or hyperactivity-impulsivity that interfere with functioning or development. This research uses a qualitative outline, more specifically using interview and observation methods. Based on the results of interviews, observations, and assessments conducted by a psychologist to the subject, the subject has attention deficit/hyperactivity disorder. The final result of this research will describe the characteristics and symptoms of ADHD experienced by the subject and examine the role of the environment, especially the family, in supporting or overcoming the challenges faced by the subjects.